Antioxidant, Anti-α-Glucosidase, Anti-Tyrosinase, and Anti-Acetylcholinesterase Components from Stem of Rhamnus formosana with Molecular Docking Study - Chia-Hsuan Tsai; Ya-Lun Liou; Sin-Min Li; Hsiang-Ruei Liao; Jih-Jung Chen (Antioxidants)
Rhamnus formosana is a creeping evergreen shrub endemic to Taiwan. In traditional medicine, Rhamnaceae plants are used as herbal remedies for conditions such as itching, difficulty urinating, and constipation. This study explores the inhibitory effects of various solvent extracts and bioactive components of R. formosana on α-glucosidase, tyrosinase, acetylcholinesterase (AChE), and antioxidant activity. The 100 °C water extract exhibited strong antioxidant activity in DPPH, ABTS, superoxide, and FRAP assays. The methanol extract demonstrated the highest α-glucosidase inhibitory effect, while the ethanol extract displayed potent AChE inhibition and the acetone extract showed the most potential tyrosinase inhibitory activity among the extracts. Five main biocomponents were isolated and evaluated for their bioactivities. Among them, kaempferol (1) and quercetin (2) exhibited notable antioxidant activity in DPPH and ABTS assays. Particularly, kaempferol (1) performed the best α-glucosidase inhibitory effect, physcion (5) showed the strongest AChE inhibition, and quercetin (2) demonstrated the most potential for tyrosinase inhibitory activity. Further molecular docking studies revealed that there may be stronger binding mechanisms between bioactive components and target enzymes (including α-glucosidase, acetylcholinesterase, and tyrosinase) than the positive control. These findings suggest that bioactive extracts and compounds from the stems of R. formosana may have potential as natural antioxidant, anti-α-glucosidase, anti-AChE, and anti-tyrosinase drug candidates or dietary supplements for the management of oxidative stress-related conditions, including hyperglycemia, pigmentation disorders, and neurodegenerative diseases.